Tabloidization versus Credibility: Short Term Gain for Long Term Pain - Spillane, Brendan; Wade, Vincent; Brady, Michael; Hoe, Isla; Wade, Vincent; Lawless, Séamus (ACM, 2020)
Print news agencies have been under pressure from falling sales and advertising revenue and increased competition. As the Internet became the dominant medium, news agencies invested heavily in their websites and apps, providing their news for free, rather than selling a print edition. Reducing the cost of production and removing access barriers such as geographic location had the potential to increase readership and advertising, covering costs and maintaining profits. Unfortunately, this business model has for the most part failed. Many higher quality news agencies are now implementing paywalls on their news websites to once again monetize their product. Others have begun to emulate the look and feel of tabloid news websites to increase readership and stickiness and advertising revenue. This study shows the negative impact of such visual tabloidization on initial impressions of credibility, which may have long term detrimental effects on the news agency. The authors would like to dedicate this paper to the memory of Professor Séamus "Shay" Lawless, the supervisor of this work who died on May 16th 2019 after fulfilling his dream of summiting Mount Everest.
CHI - The ACM Conference on Human Factors in Computing Systems
Keywords: Credibility; Tabloidization; News website design; News website aesthetics; First impressions; Creative Technologies; Credibility; Internet News; News; News Website Design; Online News; Tabloidization; tabloids; Communication